De-Rationing in the U.S.S.R. - Chossudowsky, E. M. (Review of Economic Studies, 1941)
Journal Article De-Rationing in the U.S.S.R. Get access E. M. Chossudowsky E. M. Chossudowsky Glasgow Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 9, Issue 1, November 1941, Pages 1–27, https://doi.org/10.2307/2967635 Published: 01 November 1941